Effects of dynamic stretching on energy cost and running endurance performance in trained runners - Zourdos, M. C.; Wilson, J. M.; Sommer, B. A.; Lee, S. -R.; Park, Y. -M.; Henning, P. C.; Panton, L. B.; Kim, J. S. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to examine the effects of dynamic stretching on running energy cost and endurance performance in trained male runners. Fourteen male runners performed both a 30-minute preload run at 65% V?O2max and a 30-minute time trial to assess running energy cost and performance, respectively. The subjects repeated both the trials after either 15 minutes of dynamic stretching (i.e., experimental condition) or quiet sitting (i.e., control condition) while the order was balanced between the subjects to avoid any order effect. The total calories expended were determined for the 30-minute preload run, whereas the distance covered was measured in the time trial. Average resting V?O2 increased significantly (p < 0.05) after dynamic stretching (prestretch: 6.2 ± 1.7 vs. poststretch: 8.4 ± 2.1 ml·kg-1·min-1) but not during the quiet-sitting condition. Caloric expenditure was significantly higher during the 30-minute preload run for the stretching (416.3 ± 44.9 kcal) compared with that during the quiet sitting (399.3 ± 50.4 kcal) (p < 0.05). There was no difference in the distance covered after quiet sitting (6.3 ± 1.1 km) compared with that for the stretching condition (6.1 ± 1.3 km). These findings suggest that dynamic stretching does not affect running endurance performance in trained male runners.